Interactions of the Intestinal Epithelium with the Pathogen and the Indigenous Microbiota: A Three-Way Crosstalk - C. V. Srikanth; Beth A. McCormick (Interdisciplinary Perspectives on Infectious Diseases)
The mucosal surfaces of the gastrointestinal tract harbor a vast number of commensal microbiota that have coevolved with the host, and in addition display one of the most complex relationships with the host. This relationship affects several important aspects of the biology of the host including the synthesis of nutrients, protection against infection, and the development of the immune system. On the other hand, despite the existence of several lines of mucosal defense mechanisms, pathogenic organisms such as Shigella and Salmonella have evolved sophisticated virulence strategies for breaching these barriers. The constant challenge from these pathogens and the attempts by the host to counter them set up a dynamic equilibrium of cellular and molecular crosstalk. Even slight perturbations in this equilibrium may be detrimental to the host leading to severe bacterial infection or even autoimmune diseases like inflammatory bowel disease. Several experimental model systems, including germ-free mice and antibiotic-treated mice, have been used by various researchers to study this complex relationship. Although it is only the beginning, it promises to be an exciting era in the study of these host-microbe relationships.